Retained ability to extract gist in childhood-acquired amnesia: Insights from a single case. Issue 3 (3rd May 2020) - Pauly-Takacs, Kata; Moulin, Chris J.A.
ABSTRACT: This paper presents the performance of a young amnesic person (CJ) in the DRM task. CJ was found to be sensitive to the DRM manipulation at a level comparable to controls in recognition and at a level higher than controls in free recall. Detailed analyses of recall intrusions lent further support to the finding that CJ is able to extract gist on the basis of semantic associations. Results are discussed with reference to relevant theory as well as the potential role of an impaired and immature cognitive system in adopting a semantic gist strategy in the absence of episodic memory.